Solid Phase Extraction of Mercury(II) from Natural Water by Octadecyl-Bonded Silica-Loaded Schiff's Base 4,4'-Dimethoxybenzil bisthiosemicarbazone Phases - Moghimi, Ali; Javad Poursharifi, Mohammad (Asian Journal of Chemistry, 2011)
Octadecyl-bonded silica phase loaded with 4,4'-dimethoxybenzil bisthiosemicarbazone were synthesized based on chemical binding and physical adsorption approaches. The stability of a chemically modified 4,4'-dimethoxybenzil bisthiosemicarbazone especially in concentrated hydrochloric acid which was then used as a recycling and pre-concentration reagent for further uses of octadecyl-bonded silica immobilized 4,4'-dimethoxybenzil bisthiosemicarbazone. The application of this octadecyl-bonded silica for sorption of a series of metal ions was performed by using different controlling factors such as the pH of metal ion solution and the equilibration shaking time by the static technique. This difference was interpreted on the basis of selectivity incorporated in these sulfur containing octadecyl-bonded silica phases. Mercury(II) was found to exhibit the highest affinity towards extraction by these octadecyl-bonded silica phases. The pronounced selectivity was also confirmed from the determined distribution coefficient (Kd) of all the metal ions, showing the highest value reported for mercury(II) to occur by octadecylbonded silica immobilized 4,4'-dimethoxybenzil bisthiosemicarbazone phase. The potential applications of octadecyl-bonded silica immobilized 4,4'-dimethoxybenzil bisthiosemicarbazone phase for selective extraction of mercury(II) to occur from aqueous solution were successfully accomplished as well as pre-concentration of low concentration of Hg(II) (40 pg mL-1) from natural tap water with a pre-concentration factor of 200 for Hg(II) off-line analysis by cold vapour atomic absorption analysis.